Implementing Al-Ashri Textbook in Arabic Learning: Strategies and Evaluation - Arizal, Habib; Fauji , Imam (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs a descriptive qualitative method to elucidate the process of implementing the Al-Ashri textbook in teaching Arabic to tenth-grade Multimedia students at SMK Pemuda Krian. The investigation encompasses three key phases: 1) Preparatory steps, involving student and classroom readiness, material preparation, and the adoption of an introductory mufradat learning strategy. 2) The learning process itself, where the teacher employs various techniques including the drilling method, sam'iah syafahiyah method, and qowaid wa tarjamah method, supplemented by the use of visual aids from the school environment. 3) Evaluation procedures, integrating formative and summative assessments. This research offers valuable insights into effective pedagogical strategies for Arabic language instruction, providing a framework for optimizing learning outcomes in similar educational settings. Highlight: The study delves into the implementation process of the Al-Ashri textbook for teaching Arabic to tenth-grade Multimedia students. It encompasses three vital phases: preparatory steps, diverse teaching techniques, and comprehensive evaluation methods. The research provides valuable insights for optimizing Arabic language instruction in similar educational contexts, emphasizing effective pedagogical strategies. Keyword: Descriptive Qualitative Method, Al-Ashri Textbook, Arabic Language Instruction, Pedagogical Strategies, Learning Outcomes